Machine Crafted: 3-Dimensional Machine Knitted Forms - Kalyanji, Jyoti (Auckland University of Technology, 2013)
Unrealised design capacity in computerised seamless knitting technology is highlighted in emerging research. The adoption of this technology, both in New Zealand and internationally, is largely driven by the economic gains it affords knitted garment manufacturers rather than the opportunities it presents for new design (Challis, Sayer, & Wilson, 2006; Evans-Mikellis, 2011; Smith, 2013; Yang, 2010). Complexities of the machinery and its user interface have constrained textile designers, impacting on their creative output, leaving the technology largely unexplored (Black, 2002; Mowbray, 2002). By acquiring technical skills and understanding of the seamless environment through practice-based enquiry, this research integrates computerised seamless knit technology into small-scale textile design practice; the goals are to exploit the creative potential of the technology and realise crafted design outcomes. This research results in prototypical soft furniture and homeware products.
Keywords: Seamless knitting; Textile design; WholeGarment; 3-dimensional knit; Learning methods